Diagnosis of neurosyphilis with cerebrospinal fluid pcr: a systematic review - Renan Barros Domingues; Carlos Alberto Salzedas Giafferi; Márcio Vega dos Santos; Fernando Brunale Vilela de Moura Leite; Carlos Senne (Sociedade Brasileira de Patologia Clínica, 2022)
ABSTRACT Background Neurosyphilis is difficult to be diagnosed. CSF VDRL is the gold standard, but its sensitivity is low. Cerebrospinal fluid (CSF) PCR for the detection of Treponema pallidum DNA has been evaluated; however, its diagnostic value is still poorly understood. Methods Here we performed a systematic review including articles that assessed the diagnostic sensitivity of CSF PCR in patients with syphilis and neurosyphilis. The CSF PCR sensitivity and specificity of different PCR assays was assessed in patients with neurosyphilis with or without HIV coinfection and in patients with syphilis with no central nervous system (CNS) manifestations. Results Eighteen studies evaluating 703 patients were included. The PCR sensitivity for neurosyphilis was 73.9% among HIV negative and 37.5% among HIV infected patients, having varied from 62.2% to 100% with different PCR assays. The sensitivity of CSF VDRL CSF was 68% in the same population. The specificity of CSF PCR was 93%. CSFPCR was positive in16.4% of the patients with primary and secondary syphilisand 28.9% of patients with latent syphilis. None of the syphilis cases without neurological manifestations were positive with CSF VDRL. Conclusion CSF PCR seems to be at least as sensitive as CSF VDRL, with good specificity. In addition, CSF PCR may potentially reveal early neuroinvasion in patients withsyphilis with no CNS symptoms. Future studies are still needed to assess the potential clinical value of detecting T. pallidum DNA in CSF in syphilis cases prior to the development of CNS symptoms.